(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
Cerebral palsy (CP) continues to be a leading contributor to childhood disability. The condition is often accompanied by impaired muscle strength and reduced functional independence. Despite the importance of physical therapy in the rehabilitation of children with CP, standard programs often lack selectivity regarding specific muscle groups of the upper limb. Objective. To assess the effectiveness of a modified physical therapy program in improving upper limb muscle strength in children with cerebral palsy. Methods. A total of 60 children aged 6–12 years with spastic upper limb paresis (GMFCS levels I–III) were randomized into a main group (n=30) and a control group (n=30). The main group underwent rehabilitation using a modified program incorporating targeted segmental training, proprioceptive stimulation, and progressive complexity of tasks. The control group received a standard rehabilitation protocol. Muscle strength was assessed using manual muscle testing (MMT) according to the Lovett scale at baseline and after intervention. Statistical analysis included intra- and inter-group comparisons with t-tests and significance set at p<0.05. Results. At baseline, both groups showed comparable mean values of muscle strength (3.4–4.7 points), indicating a moderate level typical for the target population. Following the intervention, both groups demonstrated positive dynamics, but the main group showed higher absolute and relative gains, particularly in proximal and forearm movements. A statistically significant between-group difference was observed only in elbow flexion on the right side (t=2.37; p=0.021), while other improvements in the main group were clinically meaningful. Conclusions. The modified physical therapy program proved more effective in enhancing upper limb strength in children with CP compared to the standard approach. The results justify its application in clinical settings and emphasize the importance of continued investigation into long-term effects and individualized rehabilitation strategies.